Fatty Acid Composition and Physico-chemical Properties of Dysoxylum binectariferum Seed Coat Oil - Parcha, Versha; Gahlot, Manoj; Rawat, M. S. M. (Indian Forester, 2003)
Oils and fats are integral part of human diet and to match the demands of ever increasing population, there is a continuous search for new edible oils. In the present study, seed coats of Dysoxylum binectariferum were examined. The plant produces seeds in abundant quantity and the seed coats are found to contain fine oil in 40% yield. The results of gas liquid chromatographic analysis indicate that the oil is rich in unsaturated fatty acids like oleic, linoleic acids which are the essential requirement of human diet. The oil also contains palmitoleic, eicosenoic and linolenic acids and saturated fatty acids i.e. myristic, stearic, arachidic and palmitic acids and is proven to be non-toxic on animal experimentation’s (rats). Since the oil is present in good yield, is non-toxic and contains essential fatty acids so has to promise to be used as an alternate source of edible oil.